Arthroscopic treatment of triangular fibrocartilage complex injuries in paediatric and adolescent patients. (July 2019) - Trehan, Samir K.; Schimizzi, Gregory; Shen, Tony S.; Wall, Lindley B.; Goldfarb, Charles A.
We assessed outcomes of 43 paediatric and adolescent patients (44 wrists) undergoing arthroscopic triangular fibrocartilage complex surgery by a single surgeon between 2003 and 2016. Medical records were reviewed for clinical, imaging, and operative data. Preoperatively, 49% of patients had additional diagnoses and mean QuickDASH was 47. Patients were telephoned to assess current wrist pain, subsequent treatment(s), satisfaction, and to complete QuickDASH and Patient-Rated Wrist Evaluation questionnaires. Twenty-five patients responded with mean follow-up of 70 months (minimum 13 months). In those patients not reached by telephone, mean clinical follow-up was 21 months. Seven patients had subsequent surgery (most commonly ulnar shortening osteotomy); this was associated with lower satisfaction scores. At final follow-up, mean QuickDASH was 4, Patient-Rated Wrist Evaluation 8 and patient and parent satisfaction scores were 9 and 9 out of 10, respectively. In conclusion, arthroscopic triangular fibrocartilage complex treatment in paediatric patients yielded favourable outcomes and patient/parent satisfaction. Level of evidence: IV